Collaboration between Islamic Religious Education Teachers and Islamic Religious Extension Workers in Drug Abuse Prevention in Labuhan Batu - Nasution, Zulkarnain; Megawati, Betti; Lubis, Lahmuddin (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
The purpose of this research is to analyze the implementation of collaboration between Islamic Religious Education Teachers and Islamic religious instructors in efforts to prevent drug abuse in Madrasah Aliyah Labuhanbatu Regency, focusing on methods, materials, as well as inhibiting and supporting factors. This research adopts a qualitative approach, utilizing data collection techniques without numerical data or nominal fractions, as field data is required. Additional research was gathered in the form of information obtained from informants. The study was conducted at MAN Labuhanbatu, MAS Darul Muhsinin, and MAS Nur Ibrahimy, employing data collection techniques including interviews, field observations, and documentation studies. Data processing and analysis techniques involved data reduction, presentation, and concluding. The research period spanned from July 20, 2023, to March 3, 2024. The findings revealed that collaboration between Islamic Religious Education Teachers and Islamic religious instructors was executed through two main activities: Focus Group Discussions (FGD) and Programming Extracurricular Activity School (PEAS). These collaborations were augmented by: a) Orientation sessions and local seminars on drug education efforts, and b) Organizing extracurricular activities, particularly in scouting, aimed at instilling anti-drug values, including those rooted in the basic principles of Scouting.